miRNA-mediated regulation of clock gene expression in men and women with colorectal cancer and possible consequences for disease management - Iveta Herichová (Biomedical Journal)
Background: The incidence and mortality of colorectal cancer (CRC) are persistently higher in men than in women. CRC malignancy is strongly influenced by small non-coding RNAs (miRNAs). Moreover, deregulation of the circadian molecular oscillator has been associated with CRC facilitation. To analyse possible cumulative effects of the above-mentioned factors on CRC progression, we focused on functions of sex-biased miRNAs associated with the clock genes per2 and/or cry2, which are involved in the cell cycle control and DNA damage response. Major findings: We identified miR-24, miR-92a, miR-181a, and miR-21 associated with per2 that are up-regulated in transformed colon tissue of men. miR-93, miR-17, miR-20a, and miR-24 with higher expression in males compared to females were linked to cry2. All these miRNAs possess oncogenic potential and exert their effects mainly via inhibition of the tumour suppressors phosphatase and tensin homolog (PTEN) and/or p53. Down-regulation of PTEN and p53 in men was further strengthened by inhibition of tumour suppressor per2. Oncogenic up-regulated miRNAs associated with per2 or cry2 in the transformed colon tissue of women were not detected. Conclusion: We conclude that the cancer-promoting, sex-biased miRNAs miR-24, miR-92a, miR-181a, miR-93, miR-17, miR-20a, and miR-21 associated with clock genes per2 and/or cry2 can contribute to the sex-dependent development of CRC via inhibition of the PTEN and p53 pathways.